Long-Term Abacus Training Induces Automatic Processing of Abacus Numbers in Children. (July 2014) - Du, Fenglei; Yao, Yuan; Zhang, Qiong; Chen, Feiyan
Abacus-based mental calculation (AMC) is a unique strategy for arithmetic that is based on the mental abacus. AMC experts can solve calculation problems with extraordinarily fast speed and high accuracy. Previous studies have demonstrated that abacus experts showed superior performance and special neural correlates during numerical tasks. However, most of those studies focused on the perception and cognition of Arabic numbers. It remains unclear how the abacus numbers were perceived. By applying a similar enumeration Stroop task, in which participants are presented with a visual display containing two abacus numbers and asked to compare the numerosity of beads that consisted of the abacus number, in the present study we investigated the automatic processing of the numerical value of abacus numbers in abacus-trained children. The results demonstrated a significant congruity effect in the numerosity comparison task for abacus-trained children, in both reaction time and error rate analysis. These results suggested that the numerical value of abacus numbers was perceived automatically by the abacus-trained children after long-term training.